2010
DOI: 10.1016/j.bmc.2010.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of Hsp90 inhibitors: Exploring the SAR of Sansalvamide A derivatives

Abstract: Utilizing the structure-activity relationship we have developed during the synthesis of the first two generations and mechanism of action studies that point to the interaction of these molecules with the key oncogenic protein Hsp90, we report here the design of 32 new Sansalvamide A derivatives and their synthesis. Our new structures, designed from previously reported potent compounds, were tested for cytotoxicity on the HCT116 colon cancer cell line, and their binding to the biological target was analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 72 publications
(104 reference statements)
3
75
0
Order By: Relevance
“…http://autodock.scripps.edu). Literature review shows that AutoDock has offered several fruitful advantages in the field of drug design [35].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…http://autodock.scripps.edu). Literature review shows that AutoDock has offered several fruitful advantages in the field of drug design [35].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…2931 To prove that SM145 inhibits the molecular chaperone function of hsp90, we performed two types of luciferase refolding assays. The first was a pure protein assay, where hsp90 and necessary co-chaperones were incubated with heat-denatured luciferase.…”
mentioning
confidence: 99%
“…This cytoprotective response is usually referred to as a heat shock response (HSR). Investigation of the SM145's mechanism showed that in contrast to the classic inhibitors, SM145 did not induce this HSR [26][27][28]. This successful discovery with SM145 drove the development of new molecules that were less hydrophobic and more potent than SM145.…”
Section: Sansalvamide Amentioning
confidence: 87%
“…Performing amino acid scans on three positions (i.e. Position I, II and III) a Gly, an L-Phe and a D-Phe or an N-Me amino acid, (Compounds 2-13, Table 1), McAlpine et al found that unlike previous work on pentapeptides [31,[41][42][43][44][45][46][47][48], the N-Me substituent was unable to lock the macrocycle into a single conformer (San B2-B4). In contrast, substitution with L-Phe or a D-Phe produced a single macrocyclic conformer (San B9, B10, B12 and B13).…”
Section: Sanguinamide Bmentioning
confidence: 93%